2012
DOI: 10.4103/0975-1483.96616
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Effects of Cleistanthin A and Cleistanthin B from the Leaves of Cleistanthus Collinus in Wistar Rats

Abstract: To study the diuretic effects of cleistanthin A and cleistanthin B, phytoconstituents were isolated from the leaves of Cleistanthus collinus in Wistar rats. The in vivo diuretic effects of cleistanthins A and B were determined according to the Lipschitz test. Prior to the experiment, the animals were fasted for 5 h and placed individually in metabolic cages. Cleistanthins A and B (12.5, 25, and 50 mg/kg) and furosemide (5 mg/kg) were suspended in 0.5% w/v carboxymethyl cellulose and administered orally. The ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In addition, EO at 150 mg/kg and citral at 75 mg/kg cause the elimination of urine only during the first 5 hours, such as furosemide. Previous work has shown that furosemide at doses between 10 and 20 mg/kg exerts its diuretic effect during the first five hours (Sanogo et al, 2009, Parasuraman andRaveendran, 2012). Also, in the mice treated with EO at 150 mg/kg, the volumetric urinary excretion is greater than 150% as in the mice that received the furosemide (20 mg/kg).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, EO at 150 mg/kg and citral at 75 mg/kg cause the elimination of urine only during the first 5 hours, such as furosemide. Previous work has shown that furosemide at doses between 10 and 20 mg/kg exerts its diuretic effect during the first five hours (Sanogo et al, 2009, Parasuraman andRaveendran, 2012). Also, in the mice treated with EO at 150 mg/kg, the volumetric urinary excretion is greater than 150% as in the mice that received the furosemide (20 mg/kg).…”
Section: Discussionmentioning
confidence: 91%
“…The compounds were reported to exert diuretic effect, and this could also have contributed to the reduction in BP. [ 14 ] Since we have not recorded the urine output in this study, the above explanation could remain as speculation only.…”
Section: Discussionmentioning
confidence: 94%
“…The dose selected for pharmacological evaluation is <1/10 of the toxic dose based on the dose determination. [ 14 ] The hypertensive control group was treated with the vehicle that is, CMC. At the end of the 5 th week again the BP was measured noninvasively to monitor the BP change in response to the test drug.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Both cleistanthins A and B are glycosides commonly present in Euphorbiaceae family plants. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%